Cover Image, Volume 97, Issue 8. (June 2017) - Shimamura, Yuko; Iio, Misako; Urahira, Tomoko; Masuda, Shuichi
Abstract : The cover image, by Yuko Shimamura et al, is based on the Research Article Inhibitory effects of Japanese horseradish (Wasabia japonica) on the formation and genotoxicity of a potent carcinogen, acrylamide, DOI:10.1002/jsfa.8055 . Abstract : The cover image, by Yuko Shimamura et al, is based on the Research Article Inhibitory effects of Japanese horseradish (Wasabia japonica) on the formation and genotoxicity of a potent carcinogen, acrylamide, DOI:10.1002/jsfa.8055 .